Molekularne povezave med cirkadianim ritmom in mikro RNA v hepatocelularnem karcinomu - Struna, Rok (Zdravniški vestnik, 2023)
Background: Circadian rhythm is regulated at the central as well as at the cellular level via transcriptional-translational feedback loops that are precisely regulated. MiRNA molecules also affect the regulation of circadian rhythm, which, together with protein complexes, lead to the silencing of the translation of certain cellular proteins. Chronic disturbance in circadian rhythm can potentially lead to malignant cell transformation. Hepatocellular carcinoma is one of the most common cancers in humans, where the influence of different signaling pathways on carcinogenesis is still unclear. We were interested in the influence of circadian rhythm and miRNA molecules on the occurrence of hepatocellular carcinoma. We focused on the influence of circadian rhythm and miRNA molecules on circular RNA expression. We also wanted to examine whether the increased expression of specific miRNA molecules affects the amount of mRNA produced for certain proteins in liver cancer cells. Methods: The experiment was performed on the Hep G2 and Huh7 cell lines. Initially, we introduced the desired molecules (hsa-miR-17 and circadian transcription factors) into the cells by the transfection process, with which we wanted to influence the expression of the genes of interest. RNA was isolated from the cells and transcribed into complementary DNA. qPCR (quantitative polymerase chain reaction) was performed, based on which we then inferred the level of expression of the desired genes. The results were processed and presented graphically. Results: By processing the results, we found that none of the three hypotheses could be confirmed, as no statistically significant difference was found in any of the expression levels of the desired genes (?= 0.05). Conclusions: Although we could not confirm the hypotheses, the research area would be worth further attention to show a more substantial influence of the factors we observed. It would be necessary to focus on specific molecules, thus gaining new targets for treating liver diseases, which would improve the patients’ quality of life and prolong their expected survival. New risk factors could also be identified to raise public awareness of prevention to reduce the incidence of HCC.
Keywords: carcinogenesis; gene expression; izražanje genov; karcinogeneza; molecular genetics; molekularna genetika